A biomechanical comparison of initial sprint acceleration performance and technique in an elite athlete with cerebral palsy and able-bodied sprinters. Issue 2 (3rd March 2020) - Bezodis, Ian N.; Cowburn, James; Brazil, Adam; Richardson, Rhian; Wilson, Cassie; Exell, Timothy A.; Irwin, Gareth
Abstract: Cerebral palsy is known to generally limit range of motion and force producing capability during movement. It also limits sprint performance, but the exact mechanisms underpinning this are not well known. One elite male T36 multiple-Paralympic sprint medallist (T36) and 16 well-trained able-bodied (AB) sprinters each performed 5–6 maximal sprints from starting blocks. Whole-body kinematics (250 Hz) in the block phase and first two steps, and synchronised external forces (1, 000 Hz) in the first stance phase after block exit were combined to quantify lower limb joint kinetics. Sprint performance (normalised average horizontal external power in the first stance after block exit) was lower in T36 compared to AB. T36 had lower extensor range of motion and peak extensor angular velocity at all lower limb joints in the first stance after block exit. Positive work produced at the knee and hip joints in the first stance was lower in T36 than AB, and the ratio of positive:negative ankle work produced was lower in T36 than AB. These novel results directly demonstrate the manner in which cerebral palsy limits performance in a competition-specific sprint acceleration movement, thereby improving understanding of the factors that may limit performance in elite sprinters with cerebral palsy.